RAISING PRAGMATIC AWARENESS IN TRANSLATION AND TRANSLATING - Engliana, Engliana (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2015)
Language competence and pragmatic competence are significant factors in translation activity, thus there should be refined instruments, tools, and methods as well as procedures in raising awareness not only on linguistic competence of translators or students translators, but also equally important on pragmatic competence. The purpose of this writing is to suggest and trigger teachers/educators teaching translation subject at the university level particularly to make use of audiovisual as tool to increase awareness of implicatures and other pragmatic components involved in translating subtitles from English to Indonesian and vice versa. In other words, the students realise that they need pragmatic awareness in the process of text transfer. The writer uses library research to explore varieties of teaching methods and procedures in teaching translation using multimedia or audiovisual. To sum up, it is achievable to enhance pragmatic awareness in teaching translation using audiovisual as long as the teachers/lecturers/educators are able to develop material and propose a model or lesson plan of raising pragmatic awareness in language teaching, especially in the context of English as a foreign language.